2021
DOI: 10.3389/fmed.2021.639152
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Intrapulmonary Arteriovenous Anastomoses in COVID-19-Related Pulmonary Vascular Changes: A New Player in the Arena?

Abstract: Up to now, COVID-19-related vascular changes were mainly described as thrombo-embolic events. A handful of researchers reported another type of vascular abnormality referred to as “vascular thickening” or “vascular enlargement,” without specifying whether the dilated vessels are arteries or veins nor providing a physiopathological hypothesis. Our observations indicate that the vascular dilatation occurs in the venous compartment, and underlying mechanisms might include increased blood flow due to inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…It is worth mentioning that the CT sign of vascular enlargement was frequently seen in severe patients during hospitalization (57.6%), but was rarely seen in non-severe ones or patients after discharge. It was reported that in patients with COVID-19, due to inflammation and the activation of arteriovenous anastomoses, venous blood flow increases and results in the vascular dilatation in the venous compartment ( 32 , 33 ). This could help to understand the sign of vascular enlargement in severe patients with COVID-19 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the CT sign of vascular enlargement was frequently seen in severe patients during hospitalization (57.6%), but was rarely seen in non-severe ones or patients after discharge. It was reported that in patients with COVID-19, due to inflammation and the activation of arteriovenous anastomoses, venous blood flow increases and results in the vascular dilatation in the venous compartment ( 32 , 33 ). This could help to understand the sign of vascular enlargement in severe patients with COVID-19 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A patient subset may have acute respiratory distress syndrome (ARDS) with a severe or even lethal disease course [ 1 , 2 ] and/or cardiovascular complications [ 3 , 4 , 5 ]. From the pathophysiological point of view, interference between pulmonary and cardiovascular consequences, with or without morphologic expression, have been debated [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, areas of oligemia have been consistently described as well [ 8 , 15 ], which are seemingly contradictory to vascular dilatation suggestive of increased blood flow and blood volume [ 18 ]. The simultaneous presence of oligemia and vascular dilatation raises the question of intrapulmonary arteriovenous shunt mechanisms that may play a role in the discrepancy between the morphological appearance on imaging and severe hypoxia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the CT scan revealed vascular congestion developed over ground-glass opacities ( Figures 1A–C ), associated with markedly dilated vessels ( Figures 2B,E ), suggesting microthrombosis lesions. These fibrosis-like lesions ( 11 ) and pulmonary vascular changes ( 12 ) related to COVID-19 have been described recently.…”
Section: Discussionmentioning
confidence: 88%